2007
DOI: 10.1089/thy.2007.0008
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Molecular Analysis for the Diagnosis of Papillary Thyroid Carcinoma Through BRAFV600E Mutation and RET/PTC Rearrangement

Abstract: BRAF(V600E) mutation detected on FNAB specimens, more than RET/PTC rearrangements, is highly specific for PTC and its routine research might well be an adjunctive and integrative diagnostic tool for the preoperative diagnostic iter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 40 publications
2
54
0
6
Order By: Relevance
“…Most studies demonstrated that the sensitivity of molecular assays has improved by combined detection of BRAF and RET/PTC. An increased sensitivity from about 42.3-69% to 56.4-78% has been reported [196][197][198].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 90%
See 1 more Smart Citation
“…Most studies demonstrated that the sensitivity of molecular assays has improved by combined detection of BRAF and RET/PTC. An increased sensitivity from about 42.3-69% to 56.4-78% has been reported [196][197][198].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 90%
“…Recent studies reported that the BRAF mutation is a highly accurate marker of malignancy for thyroid nodules sampled by FNAB [205][206][207][208][209]. However, the most frequent diagnostic problems in FNAB samples are indeterminate follicular tumors and suspicion of malignancy according to the Bethesda system.…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…The results of BRAF testing in 2766 FNA samples have been reported in 18 prospective and retrospective studies. 65,66,69,70,[79][80][81][82][83][84][85][86][87][88][89][90][91][92] Among 581 BRAF-positive nodules tested in FNA samples in these studies, 580 were papillary carcinomas on pathological examination of the resected nodules, whereas one was diagnosed as a benign nodule, 92 resulting in the false-positive rate of 0.2%. This reportedly benign nodule had a histopathological diagnosis of 'atypical nodular hyperplasia' and was not examined using modern immunohistochemical techniques that are helpful in the diagnosis of thyroid malignancy in difficult cases.…”
Section: Molecular Analysis Of Fna Samplesmentioning
confidence: 99%
“…Many molecular markers (e.g., galectin-3 (Bartolazzi, Orlandi et al 2008;Kato and Fahey 2009), cytokeratin, BRAF (Lin, Liu et al 2006;Pizzolanti, Russo et al 2007;Sapio, Posca et al 2007;Kato and Fahey 2009;Nikiforov, Steward et al 2009), RAS (Nikiforov, Steward et al 2009), RET/PTC (Pizzolanti, Russo et al 2007;Sapio, Posca et al 2007;Kato and Fahey 2009;Nikiforov, Steward et al 2009), TRK (Sapio, Posca et al 2007), Pax8-PPARγ (Kato and Fahey 2009;Nikiforov, Steward et al 2009), HBME-1(Kato and Fahey 2009), hTERT (Kato and Fahey 2009), miRNA (Kato and Fahey 2009), LOH at 10q23 (Lin, Liu et al 2006)) have been evaluated to improve diagnostic accuracy for indeterminate nodules (Sapio, Posca et al 2007;Bartolazzi, Orlandi et al 2008). Recent large prospective studies have confirmed the ability of genetic markers (BRAF, Ras, RET=PTC) and protein markers (galectin-3) to improve preoperative diagnostic accuracy for patients with indeterminate thyroid nodules diagnosed by FNA biopsy (Pizzolanti, Russo et al 2007;Sapio, Posca et al 2007;Bartolazzi, Orlandi et al 2008;Franco, Martinez et al 2009;Nikiforov, Steward et al 2009). It is likely that some combination of molecular markers will be used in the future to optimize management of patients with indeterminate cytology on FNA specimens.…”
Section: Molecular Tests Used In Thyroid Nodular Lesionsmentioning
confidence: 99%